(untitled) (Elkom: Jurnal Elektronika dan Komputer, 2025)
Technological advancements have created new opportunities in education, especially for early childhood. This research develops an Android-based educational game for children aged 4 to 6, featuring material on the introduction of letters, numbers, fruits, and animals. The application was developed using the Waterfall model, which includes requirements analysis, design, implementation, testing, and maintenance. The game was designed using Flutter and the Dart language to produce an interactive and responsive interface, equipped with engaging audio-visual features. Based on the results of Blackbox testing and User Acceptance Testing (UAT), 87% of children showed interest in the game, and 82% were able to recall the material presented. Teachers also provided positive feedback, assessing the game as an effective learning medium. Nevertheless, further additions of question variations and application performance improvements are needed to enhance the overall user experience